C. J. Thomsen’s Museum and the Three Age System: A Description in the Diary of Frances Williams Wynn, 1827 - Rowley-Conwy, Peter (Hikuin, 1984)
The interest of the late Ole Klindt-Jensen in the history of Danish archaeology is well-known. Although never a student of Professor Klindt-Jensen, I enjoyed several years as a student at Moesgård during the 1970’s; it therefore seems appropriate to place on record here the following description of CJ. Thomsen’s museum. The diary in which the description appears was written in 1827 by Miss Frances Williams Wynn (my great-great-great-great aunt). She visited the museum in the Rundetårn on August 28th ofthat year, and was shown the collections by Thomsen himself. She was clearly most impressed with Thomsen, and was fascinated by the objects she saw and the descriptions she was given.